Building a Healthier Future: A Narrative Review on Early Infant Diagnosis's Role in HIV Prevention - Emmanuel Ifeanyi Obeagu; Getrude Uzoma Obeagu (Health Science Reports)
ABSTRACT Background and Aims Early infant diagnosis (EID) is a critical intervention in the global fight against pediatric HIV, providing early identification and treatment for HIV‐exposed infants. This narrative review examines the role of EID in reducing vertical transmission, improving health outcomes, and mitigating stigma in communities. The review also explores innovations, challenges, and strategies for optimizing EID programs. Methods A comprehensive literature search was conducted across databases such as PubMed, Scopus, and WHO reports to identify relevant studies, guidelines, and program evaluations. Key focus areas included diagnostic techniques, implementation strategies, and community impacts of EID programs, with an emphasis on their integration into broader HIV care frameworks. Results EID enables the early detection of HIV in infants, allowing timely initiation of antiretroviral therapy (ART), which reduces morbidity and mortality. It also indirectly prevents postnatal transmission during breastfeeding by lowering viral loads in treated infants. Innovations such as point‐of‐care testing and digital health tools have improved access and efficiency, particularly in resource‐limited settings. EID programs have demonstrated a positive societal impact by raising awareness, reducing stigma, and fostering trust in healthcare systems. However, significant challenges persist, including logistical barriers, infrastructure limitations, and socioeconomic constraints that hinder program effectiveness. Conclusion EID is essential for addressing pediatric HIV, contributing to the elimination of vertical transmission and improving outcomes for HIV‐exposed infants. To enhance its impact, stakeholders must prioritize expanding access to diagnostic tools, strengthening healthcare infrastructure, and engaging communities through education and advocacy. EID programs not only save lives but also foster societal shifts towards inclusivity and acceptance, paving the way for a healthier, HIV‐free future.